The Drafting of Legal Contracts as an Instrument of Legal Certainty and Protection - Agung, Agung Abdul Rahman Wiyono; Purwaningtyas, Lovika Augusta (Jurnal Hukum Volkgeist, 2026)
Contracts are legal instruments that play an important role in creating legal certainty and protection for parties in civil and business relationships. Problems that often arise in practice are unclear clause formulations, imbalance in bargaining positions, and a lack of understanding of the principles of contract law, which have the potential to cause disputes. This study aims to analyze the drafting of legal contracts as instruments of legal certainty and protection. The method used is normative legal research with a legislative and conceptual approach, through a literature study of primary, secondary, and tertiary legal materials. The results of the study show that contract design that meets the requirements of a valid agreement as stipulated in the Civil Code and is based on the principles of freedom of contract, consensualism, good faith, and balance is capable of providing legal certainty and legal protection in a preventive and repressive manner. Thus, contracts that are designed systematically, clearly, and proportionally not only function as evidence but also as strategic instruments in creating fair, stable, and certain legal relationships.